Basic Characteristics of an Intensive Type of the Reproduction Process in the Regional Economy - Shkurkin, Dmitry V.; Shestopal, Sergey S.; Gurieva, Lira K.; Blaginin, Viktor A.; Gurianov, Pavel A. (International Review of Management and Marketing, 2016)
The announced subject of the paper proposes the consideration of such categories as “regional economy”, “reproduction” and “intensive type of the reproduction process”. Also, it is necessary to tell that the research material reflects regional science which is formed on the basis of classic economists' works on three vectors which they have offered: “locational vector” which task is to find a key to the most expedient dislocation place of the future enterprise; “regional vector” aiming at finding the best sizes and the structure of economy of the studied region; “complex vector” aiming at the connection of localization and regional economic issues by the common theory. Keywords: regional economy, development, reproduction JEL Classifications: P25; R58